Prevention and management of cetuximab-related hypomagnesemia. Issue 28 (1st October 2022) - Tejpar, Sabine; Taniguchi, Hiroya; Falco, Agustín; Velthuis, Erica; Valencia Pineda, Christian; Mesia, Ricard
Abstract : 321 Background: Cetuximab is an epidermal growth factor receptor monoclonal antibody indicated for the treatment of squamous cell carcinoma of the head and neck and RAS wild-type metastatic colorectal cancer. Hypomagnesemia is a reversible adverse event associated with cetuximab treatment. Here, we provide the key considerations in prevention and management of cetuximab-related hypomagnesemia events in clinical practice. Methods: A PubMed literature search was conducted for articles published between 18 March 2012 and 18 March 2022 using cetuximab and hypomagnesemia as keywords. Of the 75 articles retrieved, 20 were considered relevant and are included here.Articles were excluded if they focused on hypomagnesemia-associated clinical benefits. Data were summarized and grouped into the following categories: risk and risk factors; monitoring; prevention; and management. Results: The relative risk of grade 3/4 hypomagnesemia following cetuximab therapy appears to be approximately 1.5 times higher for colorectal cancer compared with head and neck cancer. Several risk factors have been identified including age, comorbidities, treatment duration, baseline electrolyte levels, concomitant platinum-based chemotherapy, and polypharmacy. Although the frequencies of hypomagnesemia events vary between the studies identified, data from the included meta-analyses suggest that the incidence of grade 3/4 hypomagnesemia is around 4% among patients receiving cetuximab therapy. Early and regular monitoring of magnesium levels is recommended ideally every 4 to 8 weeks, especially in patients at high risk of serious complications, and up to 8 weeks following treatment cessation. Proposed proactive prophylactic interventions include magnesium supplementation for patients with baseline magnesium levels < 1.8 mg/dL, to prevent severe hypomagnesemia. The management approach depends on the degree of hypomagnesemia, the symptoms and risk factors, and may include supplementation with oral magnesium salts and/or parenteral forms; intravenous forms may be preferred due to low bioavailability and gastrointestinal adverse events related to oral supplements. While recommendations for initiating magnesium replacement in grade 1 (> 1.2 mg/dL) and grade 2 (0.91.2 mg/dL) hypomagnesemia events vary, magnesium supplementation should be given to patients with grade 3 (0.70.9 mg/dL) or grade 4 (< 0.7 mg/dL) hypomagnesemia, due to high risk of serious adverse cardiac events. If magnesium levels do not improve or continue to decrease despite supplementation, a pause in cetuximab administration may be considered. Conclusions: Hypomagnesemia is a reversible and manageable cetuximab-related adverse event and should not interfere with treatment outcomes. A periodic check of magnesium levels during treatment with cetuximab is recommended.